Modulation of HCV reinfection after orthotopic liver transplantation by fibroblast growth factor-2 and other non-interferon mediators. Issue 6 (23rd March 2015) - Van, Nguyen Dinh; Falk, Christine S; Sandmann, Lisa; Vondran, Florian W R; Helfritz, Fabian; Wedemeyer, Heiner; Manns, Michael P; Ciesek, Sandra; von Hahn, Thomas
Abstract : Objective: In HCV infected individuals graft infection occurs shortly after orthotopic liver transplantation (OLT). We aimed to describe the composition of the inflammatory response at this time, how it affects the HCV replication cycle and identify novel proviral and antiviral factors. Design: We used a Luminex assay to quantify 50 inflammatory mediators in sera before and shortly after OLT. In vitro grown HCV based on the JFH-1 isolate were used to characterise the effects of patient sera and individual mediators on HCV. Results: Although the mediator composition is highly variable between individuals, sera drawn immediately post-OLT significantly enhance HCV infectivity compared with control sera from before OLT in about half of the cases. Among 27 non-interferon inflammatory mediators fibroblast growth factor (FGF)-2 stood out as it enhanced HCV RNA replication and release of infectious particles. The effect was concentration-dependent and detectable in dividing and non-dividing cells. Moreover, pharmacological inhibition of FGF-2 receptor signalling abrogated the enhancing effect of FGF-2 and inhibited HCV replication in the absence of serum FGF-2 suggesting that HCV replication is dependent on basal activation of the FGF-2 triggered signalling pathway. Finally, in individuals with chronic HCV infection with high viral load, serum FGF-2 was significantly higher compared with those with low viral load. Conclusions: Although no single mediator may account for this effect, serum shortly post-OLT enhances HCV infection. FGF-2 is a novel endogenous driver of HCV replication and a potential therapeutic target.